Coordination in temporary organizations: Formal and informal mechanisms at the 2016 Olympics. Issue 6 (4th June 2018) - Fernandes, Aline; Spring, Martin; Tarafdar, Monideepa
Abstract : Purpose: The purpose of this paper is to explore intra-firm coordination in temporary organizations (TOs). Specifically, it identifies and explains how operational coordination evolves over time in a particular TO: the 2016 Olympic Games Organizing Committee. Design/methodology/approach: This is an immersive case study based on qualitative analysis and longitudinal fieldwork, which allowed the observation of operational coordination in real time. The main sources of data are participant observation, semi-structured interviews, and internal documents of the TO. Findings: The findings suggest that operational coordination in TOs dealing with multiple and decentralized operations takes place through the combination of both formal and informal coordination mechanisms. Further analysis indicates a contingency logic in using these mechanisms, shaped by the presence of specific coordination challenges in different phases of work. Three main aspects influencing coordination are explored. First, it is suggested that TOs are inherently "hybrid." That is, they comprise enduring as well as temporary and centralized as well as decentralized elements. These elements change over time. Second, a formal transition phase is explored: "venueization" – a phase between planning and operation in which centralized structural elements and processes are translated to operational units. Third, since TOs present emergence and dynamism, and related challenges across various phases of work, coordination is arguably contingent on the phase of the project. Research limitations/implications: Although the findings are limited to a particular empirical context, this paper offers theoretically new insights concerning the hybrid nature of processes in TOs, the contingent use of complementary coordination mechanisms, and the importance of the venueization phase, and provides a basis for future research into operational coordination in TOs. Practical implications: The findings can help practitioners understand and identify the challenges embedded in temporary contexts and develop coordination strategies accordingly. Originality/value: This study explains how operational coordination takes place in TOs enabled by formal and informal mechanisms, which are contingently combined over time through particular coordination strategies.